2018
DOI: 10.1093/bioinformatics/bty532
|View full text |Cite
|
Sign up to set email alerts
|

On the power of epigenome-wide association studies using a disease-discordant twin design

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Since our interest is in the slope not the intercept, influence of the complexity in mean level of X-linked methylation is minimized. Moreover, the use of twins in the association analyses helped to control for genetic confounding and to achieve enriched statistical power [16]. As a result, our analysis on monozygotic twins yielded significant age-related methylation changes for CpGs escaping XCI, as well as those under XCI in females.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Since our interest is in the slope not the intercept, influence of the complexity in mean level of X-linked methylation is minimized. Moreover, the use of twins in the association analyses helped to control for genetic confounding and to achieve enriched statistical power [16]. As a result, our analysis on monozygotic twins yielded significant age-related methylation changes for CpGs escaping XCI, as well as those under XCI in females.…”
Section: Discussionmentioning
confidence: 91%
“…Then we examined the X-linked DNA methylation levels in the two sexes to characterize the different methylation patterns in relation to XCI in females and analysed the methylation levels as a function of age for different patterns in male and female samples separately. The use of Danish twins helped to control for confounding from unmeasured genetic and rearing environmental factors with enriched statistical power [6,16]. Discovery and replication were carried out in the two Danish twin cohorts and replicated results were then validated in the Scottish LBC1921 birth cohort.…”
Section: Introductionmentioning
confidence: 99%
“…We think, however, explanation of the phenomenon concerns whether the observed age-related hypermethylation change is the cause or response to aging. In this regard, the longitudinal design that links methylation change at an individual level with risk of death should provide direct estimates of the association and help with causation inference (Li et al 2018). Together with the result from Lund et al (2019), we postulate that the observed age-associated hypermethylation on the sex chromosomes in males could mainly represent an active response to the aging process that helps to maintain male survival.…”
Section: Discussionmentioning
confidence: 99%
“…Twin and family studies robustly demonstrate that genetic factors play a role in risk for MD, with heritability estimates of roughly 35% for MD and 45% for early-onset MD 9 ; these heritability estimates indicate that MD is suitable for epigenetic study using twins 10 . Moreover, a large number of genetic loci have been identified for MD, supporting the role of genetic factors in the etiology of MD 11 , 12 .…”
Section: Introductionmentioning
confidence: 87%